2019
DOI: 10.3389/fnut.2019.00163
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Concentrations After the Ingestion of Dairy and Collagen Proteins, in Healthy Active Males

Abstract: Introduction: Recent evidence suggests that the consumption of essential amino acids (AA) and/or those abundantly present in collagen may have the capacity to influence the synthesis of new collagen in ligaments and tendons, when tissue perfusion is optimized (e.g., during exercise). However, little is currently known about the bioavailability of these AAs in blood after the consumption of various collagen and diary protein sources: such information is needed to develop potentially useful dietary and supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 48 publications
(60 reference statements)
5
30
0
1
Order By: Relevance
“…3 A/B). Our findings align well with Alcock et al ( 33 ), who recently demonstrated that the ingestion of calcium caseinate and hydrolyzed casein protein do not provide sufficient glycine to increase postprandial plasma glycine availability. This is attributed to the fact that casein, like many other protein sources, does not contain much glycine (2%) when compared with other amino acids, such as leucine (10%) or proline (11%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…3 A/B). Our findings align well with Alcock et al ( 33 ), who recently demonstrated that the ingestion of calcium caseinate and hydrolyzed casein protein do not provide sufficient glycine to increase postprandial plasma glycine availability. This is attributed to the fact that casein, like many other protein sources, does not contain much glycine (2%) when compared with other amino acids, such as leucine (10%) or proline (11%) ( 34 ).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, it has been speculated that protein sources delivering large amounts of the key amino acids used for connective tissue protein synthesis (ie, glycine and proline) may be more suitable for facilitating increased connective tissue protein synthesis rates. 13 , 14 , 89 , 90 This hypothesis is discussed in the following sections.…”
Section: The Impact Of Dietary Protein On Collagen Remodelingmentioning
confidence: 99%
“…It has been proposed, therefore, that the hydrolyzation of collagen protein sources may enhance collagen protein digestion and amino acid absorption. However, Alcock et al 90 have recently examined plasma amino acid profiles in human volunteers after the ingestion of either 20 g of gelatin or 20 g of hydrolyzed collagen. The ingestion of both collagen sources resulted in similar peak glycine concentrations, and no differences were observed in total plasma amino acid availability (incremental area under the curve), despite the apparently lower molecular weight of hydrolyzed collagen.…”
Section: The Impact Of Dietary Protein On Collagen Remodelingmentioning
confidence: 99%
“…Exercise-induced adaptions as well as nutrition seems to influence connective tissue. More specifically, its alterations of material and morphological adaptions after supplementation of biologically active peptides have gained increasing attention in the scientific community [103].…”
Section: Effects On Connective Tissuementioning
confidence: 99%
“…Athletes show an increased risk of articular cartilage lesions leading to functional joint pain [120]. One therapeutic attempt includes the treatment and prevention of degenerative articular processes by stimulation of collagen synthesis with biologically active peptides [103].…”
Section: Effects On Cartilage and Functional Joint Painmentioning
confidence: 99%